Pantai Jodoh Sebagai Salah Satu Destinasi Wisata di Desa Angkue Kecamatan Kajuara Kabupaten Bone - Yuyun Aida Putri (Rayhan Intermedia, 2022)
This study examines the use of the coast as modern tourism in Angkue Village, Kajuara District, Bone Regency, including: beach development as contemporary tourism as well as the role of local government and community participation in the management of matchmaking beaches as contemporary tourism. The results of this study indicate that the use of the coast as a tourist space has great potential in the progress of villages and communities. The village government in this case acts to establish policies, strategies in planning and regional development, as a facilitator for level 1 manipulation (manipulation) and level 2 Therapy (Recovery), which is included in the Non-Participant category. the form of assistance is education, training and improving skills in the business sector, and the role of the Stimultor, namely the government stimulates the development of planning businesses through special actions in influencing companies to enter the region.